WHERE WOULD WE BE WITHOUT CHEMISTRY? - Atkins, Peter (SCHOOL SCIENCE, 2011)
This year sees the world celebrating the International Year of Chemistry. The celebrations are wholly justified because chemistry is hugely important for all of us, wherever we live. If you were to strip away all the contributions of chemistry to the modern world, you would find yourself back in the stone age, life would be short and painful, you would be underfed, there would be little colour in the world, you would be dressed in skins and surrounded by few of the appliances that entertain us and ease our lives. I will admit from the outset that chemistry, like any great enterprise, does cause problems. It is used to make the explosives used in armaments. It creates poisons and the effluents of chemistry plants can ruin the environment. In some dreadful cases, accidents have killed and maimed thousands. The explosion at the Union Carbide Plant in Bhopal in India in 1984 blighted thousands of innocent lives and the terrible consequences are still with us today. Pollution of water and air has wrought havoc with our surroundings. These disadvantages and horrors have to be acknowledged — but all technological and scientific advances bring difficulties in their train. We should weigh them against the advantages. With some exceptions, the chemical industry is well aware of its obligations to humanity and environment and does what it can to avoid the potentially damaging effects of its activities. In this article, I shall concentrate on the positive contributions that chemistry makes to the modern world and leave you to judge whether the price is too high.